Land Governance and Agricultural Sustainability in Nigeria - Olubunmi Olanike Alawode; Victor Oluwadamilare Abegunde; Oluwatosin Adejoke Adewusi (African Journal on Land Policy and Geospatial Sciences, 2019)
This paper analysed land governance and crop commercialization in Nigeria. General Household Survey (Living Standard Measurement Survey) panel data for the post-planting and post-harvest periods of 2015 and 2016 cropping seasons were used. Descriptive statistics, Crop Commercialization Index (CCI) and Tobit regression model were used to analyse data. The semi-subsistence farmers constitute the highest proportion (62.4%), out of which almost one-quarter (24.6%) of the farmers sold less than a quarter (<25.0%) of their crop produce, except South West, where mean CCI of 63.71 (±30.48) indicates that more than half of farmers’ crop produce were sold, implying that the zone driving commercialization in Nigeria is the South West. Access to land through rent had positive significant effect on CCI at 1% level, contributing to agricultural sustainability and economic development. The emerging dynamic land markets will complement the Government based land allocation which are oftentimes characterized by inconsistency in land accessibility.